Smart Monitoring Temperature and Humidity Based on Incubator System using IoT - Abdullah, Hakiman; Hamdan, Rohaiza (Evolution in Electrical and Electronic Engineering, 2023)
In this study, one of the most important factors to take into consideration in chicken farms is egg fertilization. To make the monitoring of the incubation system easier for the user, the smart incubation system is built to integrate IoT technology with a smartphone. The incubator is first constructed with the setting and the hatcher combined into a single machine, including both still air and forced air incubation, and paying attention to the three parameters of temperature, humidity, and egg-turning system while monitoring the incubator. The prototype is constructed of hardware and software that can connect to the internet and monitor and control the temperature and humidity reading to maintain such conditions. The components that were used in this project included an ESP8266 module to link the microcontroller to the internet, an Arduino MEGA 2560 microcontroller for data processing, a DHT11 sensor for detecting the temperature and humidity of the incubator, a 12 VDC cooling fan and a 40W bulb to control the parameters, and finally, a Blynk app to display the collected data. The results showed that the prototype can regulate the temperature and humidity through the fan and bulb when there is a change in the settings.